The impact of passive immunisation against BMPRIB and BMP4 on follicle development and ovulation in mice - Al-Samerria, S.; Al-Ali, I.; McFarlane, J.; Almahbobi, Ghanim (BioScientifica Ltd., 2015)
The primordial follicle reserve is the corner stone of female fertility and determines the longevity and quality of reproduction. Complete depletion of this reserve will lead to primary infertility, and the key-limiting step of follicle depletion is the transition from primordial to primary follicles. It has been reported that this process is gonadotrophin-independent, but other conflicting reports are indicated otherwise and this discrepancy needs to be unequivocally clarified. The aim of this study was to investigate the role of bone morphogenetic proteins (BMPs) in the regulation of folliculogenesis in mice passively immunised against BMP receptor 1B (BMPRIB) and BMP4. While a stereological study revealed that the numbers of primordial follicles in immunised mice were significantly higher when compared with control animals, treatment with equine chorionic gonadotrophin showed no effect. In parallel, immunofluorescence microscopy revealed the presence of BMPRIB but not FSH receptor in primordial follicles. The number of primary follicles in immunised mice were also significantly increased when compared with control animals. After puberty, the rates of depletion of primordial and primary follicles were increased with age, particularly in treated animals; however, there was no significant difference between the treatment groups of the same age. Based on these results together with our previous reports in sheep and mice, we confirm that the attenuation of BMP signalling system can be an effective approach to sustain the primordial follicle reserve while promoting the development of growing follicles, ovulation and consequently overall female fertility.